Confidence in the future among the Bashkirs and Tuvans as an indicator of human development: Correlation with family status - Burkhanova, Flura B. (The New Research of Tuva, 2022)
The article examines the results of a survey of the Bashkirs and Tuvans who live in the republics of Bashkortostan and Tuva. It was conducted in 2021 in order to find out the degree of their confidence in the future. The following questions were clarified: How does family status (marital status, number of family members, parental status and number of minor children) affect confidence in the future? How is confidence in the future related to subjective indicators of human development that reflect three sectors of life (income, health, education).The results of the study showed that the majority of the Tuvans and Bashkirs are confident in their future. In both ethnic groups, confidence is stronger in young people with higher and incomplete higher education and in those who live in rural areas and have regular jobs. Uncertainty is more common among the elder people, as well as among those who have a low level of education. It is also associated with urban lifestyle and the employment statuses “unemployed” and “I have a temporary job”. It has been found out that official marital and parental statuses reduce confidence. On the contrary, people who are unmarried and have no children, i.e. they live alone or as a childless couple, are more confident.The data show that the Tuvans generally consider areas of their lives (income, health, education and work) worse. They feel themselves poorer, much more often dissatisfied with their financial situation and living conditions than the Bashkirs do. They assess their health and possibilities for its support as worse. The Tuvans also have lower estimates of their opportunities for study and professional development.Confidence in the future among both the Tuvans and Bashkirs is directly and positively related to all subjective indicators of human potential development. Estimates of health status and income affect confidence the most among the Bashkirs, while among the Tuvans so does satisfaction with health opportunities and financial situation (the better the estimates, the higher the proportion of confident people).
Keywords: confidence in the future; human development; family; family status; Bashkirs; Tuvans; ethnos; standard of living; Republic of Tuva; Republic of Bashkortostan